Nurse perception on the care provided to patients with COVID-19 in the intensive care unit - Irigoin Mazabel, Jhon Elmy (2022)
Objective: To describe, analyze and understand the nurse's perception of the care provided to patients with COVID-19 in the Intensive Care Unit, Chiclayo 2021. Method: The study was qualitative, with descriptive design. The population consisted of 69 ICU nurses; the sample consisted of 15 nurses of which 8 were from the Regional Hospital, 3 from the Luis Heysen Incháustegui Hospital and 4 from the Almanzor Aguinaga Asenjo Hospital; the sample size was determined by convenience sampling with snowball technique. The instrument was a semi-structured interview, with prior informed consent using the ZOOM platform; the information was analyzed using the content analysis method. Ethical principles and scientific criteria were considered in the research. Main results: Three categories emerged as results: I. Describing personalized and comprehensive care to the patient with COVID-19 in the ICU; II. Prioritization of care based on the needs of the patient with COVID-19 and III. Attitudes and feelings when caring for the patient with COVID-19. Overall conclusion: Nursing care is important, personalized, demanding, demanding, thorough, dedicated and specialized, considering the patient with COVID-19 a pan-dimensional being focusing on his physical, emotional and spiritual dimension; committed to their work the nurses presented feelings of guilt, sadness, anxiety, stress and worry about contagion with positive, empathic and fighting attitudes.   Keywords: perception, care. Descriptors: nurse (D009726), COVID-19 (Coronavirus infections) (D018352), intensive care (critical care) (D003422). Source: DeCS